La fureur de gagner, la rage de perdre. Étude contrastive de colere, rage et fureur en français et en grec moderne - Fabienne Baider; Maria Constantinou (Études romanes de Brno, 2014)
The article sets out to examine, from a contrastive point of view, the concepts as being expressed by the lexical units colère, rage and fureur and their equivalents in Greek θυμός, οργή and λύσσα. Based on the observation drawn from previous studies that this paradigm may vary in intensity, polarity and physical and psychological manifestations, in this study we aim to study their semantic plurality due to their polysemy, in order to explain the contexts of usage which seem to be distinctive in particular for rage and fureur and then to identify their quasi-equivalents in Greek. The methodology of this study is based on lexical co-occurrences and assumes that any linguistic unit acquires its meaning in context. In this perspective, the study is based on the notion of "combinatorial profile" proposed by Blumenthal (2006) and isotopy developed by Rastier (1987). Operations of semantic features intersecting, such as virtualization and activation of these semantic features, are considered the source of meaning change in context. At the end it concludes with lexicographical proposals in order to differentiate equivalencies given so far for this paradigm.